Some Outcomes Involving a Specific Class of Functions over Differential Subordination and Superordination - Mustafa I. Hameed; Shaheed Jameel Al-Dulaimi; Kayode Oshinubi; Hussaini Joshua; Ali F. Jameel; Israa A. Ibrahim (مجلة بغداد للعلوم, 2024)
This work investigates several aspects of differential subordination and superordination, leading to the inclusion of a specific class within the domain of univalent meromorphic functions in a perforated open unit disc and deriving a few sandwich theorems. The purpose of this article is to look into a few of the characteristics of variation subordination for analytic univalent functions over a perforated unit disc. It additionally aims to shed insight into geometric characteristics like coefficient inequality, Hadamard product characteristics, and the Komatu integral operator. A few interesting findings have been discovered for variations in subordination as well as superordination in analytic univalent functions. The outcomes about variations in subordination, including linear algebra operators, were presented employing convolutions involving two linear operators. Everyone evaluates and investigates subordinations as well as superordinations about convolutions using includes from the Komatu integral operator. The convolution operator as a tool was used for obtaining multiple findings over differential subordination within the perforated unit disk employing a generalized hypergeometric function. Appropriate classes of acceptable functions are examined, and the two-dimensional real estate of the differential subordinations is explained by utilizing the linear operator, a technique that Srivastava introduced as well as examined. This leads to the establishment of several sandwich-type theorems for a class of univalent analytical functions. The current work examines several subclasses of star-like functions that are defined by subordination. Additionally, our team provides some relevant links between the results reported here and those acquired previously.